The Crisis of the Ethics of Audit Profession: Collapse of Enron Company and the Lessons Learned - Albeksh, Hasen Mohamed A. (Scientific Research Publishing, Inc., 2016)
The aim of this study is to describe and analyze the reason of collapse of the biggest energy company, the American company Enron, which is considered one of the events that has a great effect on the profession of accounting and auditing. This study focuses in the ethics, which is considered as a preventer and a conservator of the occurrence of collapses and financial scandals. The descriptive analysis approach was adopted, which depended on the inductive methodology by inducting the studies and researches which aimed to explain and analyze the reasons of the collapse of Enron company and knowing the lessons learnt from it and the methods to avoid financial scandals like this. We are going to summarize some lessons that can be learnt to avoid the same fate of Enron and regain trust of the financial markets as well as both professions of accounting and auditing. This study is divided into an introduction and four parts and a conclusion. The results find that there are many reasons of the collapse of Enron company, the most important is, the administration of the company made inflation of the profits ostensibly up to billion dollars in the year before the company’s collapse. Moreover, the internal audit in the company failed in the ethical and financial aspects as a result of continuous deception, greed, bribery, speculation and fraud.
Keywords: 8. Economic growth